Placing GIS and NLP in Literary Geography: Experiments with Literature in Portuguese. - Santos, Diana; Alves, Daniel (International Journal of Humanities & Arts Computing: A Journal of Digital Humanities, 2023)
In this case study we discuss different approaches to the study of literature in digital humanities and try to join two methodologies, namely distant reading and spatial analysis. We first describe shortly the two projects involved, the Atlas of Literary Landscapes of Mainland Portugal and Literateca, highlighting and quantifying the different ways to deal with place in literature in Portuguese. Then we describe some different paths to compare and harmonize the two approaches, focusing on annotation, extraction and geocoding of place names.